A tale of two cities - Dickens, Charles, 1812-1870.; Barnard, Frederick, 1846-1896. (Boston Books, Inc.)
The works of Charles Dickens, volume VI.
In Library storage.
Not dated. This edition contains all the copyright emendations made in the text as revised by the Author in 1867 and 1868. Cleartype edition.
Keywords: France -- history -- history -- fiction